2017
DOI: 10.1177/0269881117722987
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying metabolic disturbances associated with psychosis and antipsychotic drug treatment

Abstract: The increase in cardiovascular disease and reduced life expectancy in schizophrenia likely relate to an increased prevalence of metabolic disturbances. Such metabolic risk factors in schizophrenia may result from both symptom-related effects and aetiological factors. However, a major contributory factor is that of treatment with antipsychotic drugs. These drugs differ in effects on body weight; the underlying mechanisms are not fully understood and may vary between drugs, but may include actions at receptors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…There are a number of mechanisms by which antipsychotic medication may increase body weight, particularly blockade at D2/3, 5HT2c and histamine 1 receptors (Karr et al, 2019;Reynolds and McGowan, 2017). There is also evidence that antipsychotic medication may disrupt hormones involved in the control of food intake, such as leptin and adiponectin, and evidence that antagonism of muscarinic M3 receptors on pancreatic β-cells may contribute to glucose dysregulation (see Reynolds and McGowan, 2017). Large, multiple-treatments, network meta-analyses of clinical trials of antipsychotic medications have shown that most can lead to significant weight gain (Huhn et al, 2019;Leucht et al, 2013).…”
Section: Metabolic Adverse Effects Of Antipsychotic Medicationmentioning
confidence: 99%
“…There are a number of mechanisms by which antipsychotic medication may increase body weight, particularly blockade at D2/3, 5HT2c and histamine 1 receptors (Karr et al, 2019;Reynolds and McGowan, 2017). There is also evidence that antipsychotic medication may disrupt hormones involved in the control of food intake, such as leptin and adiponectin, and evidence that antagonism of muscarinic M3 receptors on pancreatic β-cells may contribute to glucose dysregulation (see Reynolds and McGowan, 2017). Large, multiple-treatments, network meta-analyses of clinical trials of antipsychotic medications have shown that most can lead to significant weight gain (Huhn et al, 2019;Leucht et al, 2013).…”
Section: Metabolic Adverse Effects Of Antipsychotic Medicationmentioning
confidence: 99%
“…SGAs, such as olanzapine (OLZ), have numerous metabolic side effects (Newcomer, 2005). These include weight gain, dyslipidaemia, hyperglycaemia, insulin resistance, and an increased risk for the development of type 2 diabetes and cardiovascular disease (Bergman and Ader, 2005;Newcomer, 2005;Kessing et al, 2010;Lord et al, 2017;Reynolds and McGowan, 2017). Although impairments in glucose homeostasis often accompany weight gain itself, there is evidence that OLZ has direct diabetogenic effects independent of changes in body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been tremendous reports on the metabolic side effects of atypical antipsychotic drugs, the mechanisms remain elusive (Reynolds and McGowan, 2017). Available evidence has suggested that the clinical responses to antipsychotics and related side effects could vary from patient to patient.…”
Section: Introductionmentioning
confidence: 99%